Chemical capture of diazo metabolites reveals biosynthetic hydrazone oxidation - Katarina Pfeifer; Devon Van Cura; Kelvin J. Y. Wu; Emily P. Balskus (Nature, 2026)
Abstract Chemically reactive microbial natural products have enabled therapeutic development 1 via their well-established anticancer, antibiotic and antioxidant activities. However, discovery of reactive metabolites is particularly challenging because they may not tolerate traditional bioactivity-guided isolation workflows 2 . Diazo-containing natural products are a subset of highly reactive microbial metabolites that display potent bioactivity 3 and enable powerful biosynthetic transformations 4,5 ; however, instability of the diazo group to light 6 , heat 7 , mild acid 8 and mechanical shock 9 has precluded their efficient discovery and application. Here we develop a reactivity-based screening approach to capture diazo-containing metabolites and facilitate their discovery by mass spectrometry. This workflow revealed two novel diazo-containing natural products, 4-diazo-3-oxobutanoic acid ( 1 ) and diazoacetone ( 2 ), from the human lung pathogen Nocardia ninae . Biosynthetic investigations revealed a distinct enzymatic logic for diazo formation involving hydrazone oxidation catalysed by the metalloenzyme Dob3, and its biochemical characterization suggests promising future applications in biocatalysis. Overall, our work highlights the power of reactivity-guided strategies for identifying reactive metabolites and facilitating the discovery of unique enzymatic transformations.